Labor leaders and an Australian Republic: 1999–2019. Issue 1 (2nd January 2021) - Jones, Benjamin T.
Abstract: The creation of an Australian republic has been official Australian Labor Party policy since 1991. During the 1990s Labor actively campaigned for an Australian republic under the prime ministership of Paul Keating. Following the defeat of the republic referendum on 6 November 1999, Labor leaders have continued to support the issue with varying levels of enthusiasm. This article traces the attitudes of Labor leaders to an Australian republic between 1999 and 2019 and divides them into three broad camps: revivalists, denialists, and idealists. Based on their experiences, it offers three policy recommendations if a republic is to become a reality. The first of these is that strong leadership and personal commitment is required. The second is that a plebiscite on the model is vital to later referendum success. Finally, reconciliation must not be divorced for the republic issue.